THE CONTRIBUTION OF TAṢAWUF ULAMA IN PRESERVING ḤADITH THROUGH THE TAḤQĪQ TRADITION: A FIGURE STUDY OF SHAYKH NAJMUDDĪN AL-KURDI - Bachtiar, Hafizh Ilham (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2022)
This research examines the contribution of Shaykh Najmuddīn al-Kurdī as a Tasawuf scholar in maintaining hadith through the taḥqīq tradition. Shaykh Najmuddīn al-Kurdī is a murshid of the Naqsyabandiyah order in Egypt who performs taḥqīq of several ḥadith books. In order to reveal the extent of his contribution to the study of ḥadith, this library research examines his taḥqīq’s works from two primary sources, namely the book Fatḥ al-Wadūd and the book Miṣbāḥ al-Zujājah fī Zawāid Ibn Mājah. Through this, it is known that Shaykh Najmuddīn al-Kurdī has contributed to the publication and taḥqīq of several books of ḥadith. In doing taḥqīq, he several times added comments and takhrīj. The methods used in taḥqīq are: First, explaining the details of the narrator, both in terms of his name or nickname as well as the fact that the narrator's identity is often confused with others. Second, giving reviews or explanations on vague sentences that are difficult to understand, by adding parentheses to distinguish between the explanatory sentences that he appears and the original sentences from the author. [Penelitian ini mengkaji kontribusi Syekh Najmuddīn al-Kurdiī sebagai ulama Tasawuf dalam menjaga hadis melalaui tradisi taḥqīq. Syekh Najmuddīn al-Kurdī merupakan mursyid tarekat Naqsyabandiyah di Mesir yang melakukan taḥqīq beberapa kitab hadis. Dalam rangka mengungkap sejauh mana kontribusinya dalam studi hadis, penelitian kepustakaan ini melakukan telaah atas kitab-kitab yang ia taḥqīq dengan dua sumber primer, yaitu kitab Fatḥ al-Wadūd dan kitab Miṣbāḥ al-Zujājah fī Zawāid Ibn Mājah. Melalui hal itu, diketahui bahwa Syekh Najmuddīn al-Kurdī memiliki kontribusi dalam penerbitan dan taḥqīq beberapa kitab hadis. Dalam melakukan taḥqīq, ia beberapa kali menambahkan ulasan serta takhrīj. Adapun metode yang digunakan dalam mentaḥqīq kitab adalah: Pertama, menjelaskan detail sosok perawi, baik dari segi nama atau julukannya maupun fakta sosok perawi yang identitasnya sering tertukar dengan orang lain. Kedua, memberi ulasan atau penjelasan pada kalimat samar yang sulit dipahami, dengan menambahkan tanda kurung untuk membedakan antara kalimat penjelas yang ia munculkan dan kalimat asli dari penulis.]